212k views
4 votes
Simplify the following expression.
(5^3)^5

2 Answers

3 votes

Answer: 5^15

The rule used is (a^b)^c = a^(b*c)

If you raise some exponential expression to another exponent, then you multiply the exponents. You keep the base the same.

In this case, a = 5, b = 3, c = 5.

Using a calculator,

5^15 = 30,517,578,125

But it's likely your teacher will want you to keep the answer in exponential form since it's easier to work with.

User Fahad Sarfraz
by
5.3k points
6 votes

Answer:

5 ^15

Explanation:

(5 ^3)^5 =5 ^(3×5)=5 ^15

User Sop
by
4.8k points